Perfil, dificuldades, demandas e estratégias de um grupo de idosos no uso dos medicamentos em uma UBS no município de Maracanaú-CE - Albuquerque, Francisca Maria Dias (2012)
Population ageing has been undergoing a demographic and epidemiological process.Hence, the simultaneous emergence of chronic diseases affecting mostly the elderly and requiring the use of medicine to keep those conditions under control. This research intends to identify the profile of a group of elderly from a basic health care unit (Unidade Básica de Saúde-UBS, in Portuguese)in the town of Maracanaú, CE. Its approach is qualitative, descriptive and exploratory. Data were collected in January, 2012, by use of a research tool, semistructured interview, which addressed the socio-demographic profile, amount of medicine, daily intake, morbidities, prescribed medication and difficulties concerning its usage We resorted to the software Statistical Package for the Social Science (SPSS) and content analyses to analyze the data. A total of 36 elders 10 males and 26 females, between 60 and 83 years old, with an average age of 70 for both sexes undergoing outpatient follow-up at a basic healthcare unit (Unidade Básica de Saúde-UBS, in Portuguese)in the town of Maracanaú, CE, participated in this survey. Four difficulties with the use of medicine mentioned by elders were highlighted: failure to understand doctor s prescription,. failure to identify medicine, orientation disability, poor schooling . We draw attention to the socio-demographic aspects affecting the doctor s prescription understanding, too brief an interaction between patient and health care professionals,during appointments and scheduling time frame; medicine intaking period prevents elders from getting familiar with pharmaceutical drug names; the sorting out of their medication deserves close attention, as it is a key factor for leading a healthy life. Difficulty in recognizing medicine can be explained by minor differences in size and sometimes in color found in the almost identical packages of medicine distributed by the Brazilian Unified National Health System (Sistema Único de Saúde SUS, in Portuguese). Failure in understanding doctor s prescription undermines the commitment to treatment, and, thus, increases the risk of potential drug interaction, iatrogenic conditions and hospitalization. Despite being more frequently oriented by health care system professionals, female patients are more commonly vulnerable to chronic diseases, receive more medication, perform self-medication and make wrong use of their medicine more often, as compared to male patients. The sociodemographic peculiarities of the elderly pinpoint the need for collective and individual action concerning medicine intaking. We believe that, this study shall play an important role in providing guidelines and strategies which might help the elders to make proper use of their medication